Effect of Weed Control Practices and Fertilizer Types on the Growth and Yield of Bell Pepper (Capsicum annum L.) in Nsukka Nigeria - Vivian Ogechi Osadebe; Nathaniel Dauda; Benedict Unagwu; Amarachi Nwoja; Chinedu Felix Amuji; Uchenna Noble Ukwu; Arinze Donald Uzoigwe (Journal of Agricultural Extension)
A field experiment was conducted in 2021 at the Teaching Farm of the Department of Crop Science, University of Nigeria, Nsukka, located in the derived savanna agroecology. The treatments were weed control practices comprising black polyethylene mulch, un-weeded plot, and manual weeding with hoe at 2-week intervals and different fertilizer types comprising cow dung, pig dung, and poultry manure at 20 t/ha, respectively; NPK fertilizer at 150 kg/ha; and no fertilizer (control). There were 15 treatment combinations arranged in a randomized complete block design (RCBD) replicated three times. The objectives were to ascertain the effect of weed control practices and different fertilizer sources for optimum growth and yield of bell pepper. The study revealed that the plots mulched with black polyethylene and poultry manure recorded a significantly higher number of leaves per plant (82.0), plant height (16.47 cm), a lower number of broadleaved weeds (1.45/0.5m2), grasses (1.50/0.5 m2), and sedges (0.70/0.5m2), weed dry weight (0.81 g), and higher weed control efficiency (86.48%). It could be concluded that applying black polyethylene mulch with the application of NPK or poultry manure provided positive results for growth as well as weed control and therefore should be recommended for efficient production of bell pepper.